A case of NUT midline carcinoma with no HPV infection, slight EWSR1rearrangement and strong expression of EGFR. Issue 4 (July 2013) - Maffini, Fausto; French, Christopher Alexander; Cameron, Michael James; Stufano, Viviana; Barberis, Massimo; Pisa, Eleonora; Manzotti, Michela; Cattaneo, Augusto; De Fiori, Elvio; Viale, Giuseppe
NUT midline carcinoma (NMC) is a rare neoplasm with a poor prognosis and involving mostly young patients. Here we describe a classic NMC with a BRD4-NUT fusion gene in a middle-aged woman. We also analyzed some biological features that could potentially influence its clinical behavior such as HPV infection, EWSR1 rearrangement, and the status of the EGFR gene.